Pengembangan Bahan Ajar Fisika Terapan Berbasis Scientific pada Program Studi Nautika - Nelfi Erlinda; Melda Yanti; Lelfita Lelfita (Institut Agama Islam Sunan Giri Ponorogo, 2026)
This study aimed to develop a scientific-based Applied Physics textbook for cadets of the Nautical Study Program at Politeknik Pelayaran Sumatera Barat, to identify the development process, to evaluate the quality of the product, and to determine cadets’ responses toward its use. The study employed a Research and Development (R&D) method using the ADDIE model consisting of Analysis, Design, Development, Implementation, and Evaluation stages. The research subjects included expert validators and cadets of the Nautical Study Program in the 2025/2026 academic year. Data were collected through interviews, expert validation questionnaires, and cadet response questionnaires. The data were analyzed using descriptive quantitative and qualitative techniques. The results indicated that the scientific-based Applied Physics textbook was successfully developed according to the learning needs of Nautical cadets. The textbook integrates Applied Physics concepts with maritime contexts and incorporates the scientific learning stages of observing, questioning, collecting information, associating, and communicating. The expert validation results obtained an average score of 3.54, categorized as highly feasible, while the cadets’ responses achieved an average score of 3.44, categorized as very good. These findings demonstrate that the developed textbook possesses good quality, is suitable for use in learning activities, and supports both conceptual understanding of Applied Physics and the development of cadets’ creative thinking skills.